ANALISIS KLASTER INDUSTRI PENGOLAHAN KARET DENGAN PENDEKATAN DIAMOND DI INDONESIA - Erfit, Erfit; Putra, Dios Nugraha (Jurnal Riset Manajemen dan Bisnis (JRMB) Fakultas Ekonomi UNIAT, 2020)
Purpose- This study aims to look at the profile, SWOT analysis, institutional and policy aspects of the rubber processing industry cluster in Indonesia.Design/methodology/approach- This research is secondary data research with a qualitative approach. SWOT analysis is used to analyze data, so we get Strengths, Weaknesses, Opportunities, and Threats to formulate the next strategy. Findings- The results showed that Indonesia has a great potential for the development of the rubber processing industry, this is because Indonesia is the second-largest rubber producer in the world after Thailand. The development of rubber in Indonesia is broad and its production tends to increase every year during the period 2008 - 2017. Implications- Some institutions in the rubber processing industry in Indonesia are still dominated by farmer / joint groups, cooperatives, Gapkindo, APBI. These institutions have not yet played an optimal role in order to encourage the development of the rubber processing industry in partnership programs, plantation revitalization, replanting, and downstream agro-industry. Keywords: Industrial cluster, SWOT Analysis, Development Policy